Functional variation in a key defense gene structures herbivore communities and alters plant performance - Adam, Nora (PLoS One, 2018)
Plant genetic diversity structures animal communities and affects plant population productivity. However, few studies have investigated which traits are involved and the mechanisms mediating these effects. We studied the consequences of varying the expression of a single biosynthetic gene in jasmonate (JA) defense hormones, which are essential for defense against herbivores but constrain plant growth, in experimental mesocosm populations of wild tobacco (Nicotiana attenuata) plants under attack from three native herbivores. Empoasca leafhoppers preferentially attack JA-deficient N. attenuata plants in nature, and the specialist Tupiocoris notatus mirids avoid Empoasca-damaged plants. However, in experimental mesocosm populations having equal numbers of wild-type (WT) and JA-deficient plants that are silenced in the expression of the biosynthetic gene lipoxygenase 3 (LOX3), Empoasca sp. attacked both genotypes. Empoasca sp. damage, rather than JA, determined T. notatus damage, which was reduced in mixed populations. The growth of specialist Manduca sexta larvae was reduced on WT vs. asLOX3 monocultures, but differed in mixtures depending on caterpillar density. However, seed capsule number remained similar for WT and asLOX3 plants in mixtures, not in monocultures, in two experimental scenarios reflecting high and low caterpillar attack. At high caterpillar density, WT plants growing in mixtures produced more seed capsules than those growing in monocultures while seed production of asLOX3 plants did not differ by population type. However, at low caterpillar density, asLOX3 plants growing in mixed populations produced more seed capsules than those growing in monoculture, while seed capsule production did not differ for WT by population type. Thus, mixed populations had a more stable output of seed capsules under the two scenarios. This may result from a balance between JA-mediated herbivore defense and plant competitive ability in mixed populations.